2014
DOI: 10.4187/respcare.03180
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Quality of Life Improvements of Patients With Idiopathic Pulmonary Fibrosis Completing a Pulmonary Rehabilitation Program

Abstract: INTRODUCTION: Pulmonary rehabilitation is effective for patients with COPD, but its benefit is less clearly established in idiopathic pulmonary fibrosis (IPF), especially in regard to levels of physical activity and health-related quality of life. The objectives were to determine whether pulmonary rehabilitation increased physical activity as assessed by the International Physical Activity Questionnaire (IPAQ), and improved quality of life and symptoms as assessed by the St George respiratory questionnaire for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
103
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(112 citation statements)
references
References 29 publications
(43 reference statements)
2
103
0
7
Order By: Relevance
“…In addition, as LTx candidates with chronic disease are more prone to exercise limitations, preoperative physiotherapy (PP) can improve exercise tolerance (1), which in some patients, is severely impaired, often leaving them housebound. Specifically, a rehabilitation program including supervised aerobic and strengthening exercises can significantly improve symptoms and physical activity levels in idiopathic pulmonary fibrosis (IPF) patients (2). IPF is a chronic progressive disease of unknown etiology that affects mainly adult men; the symptoms of IPF are mainly shortness of breath and cough.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as LTx candidates with chronic disease are more prone to exercise limitations, preoperative physiotherapy (PP) can improve exercise tolerance (1), which in some patients, is severely impaired, often leaving them housebound. Specifically, a rehabilitation program including supervised aerobic and strengthening exercises can significantly improve symptoms and physical activity levels in idiopathic pulmonary fibrosis (IPF) patients (2). IPF is a chronic progressive disease of unknown etiology that affects mainly adult men; the symptoms of IPF are mainly shortness of breath and cough.…”
Section: Introductionmentioning
confidence: 99%
“…The educational approach must be directed to the surgery, the professional team must prepare the patient to the intervention as well as his/her recovery that will need care and physical training follow-up in the PR (31) . The evaluation protocols of the analyzed studies (lung function, QoL, exercise capacity and quadriceps force) were similar to other studies in different patients (11,12,15,16) . Recent study (32) showed that the delay in the recovery of the exercise capacity after lung transplant is not associated with the delay in the improvement of the function of the transplanted organ but it results to the slow recovery of the muscular force.…”
Section: Discussionmentioning
confidence: 60%
“…It is a multidisciplinary program based on a thorough patient assessment followed by patient-tailored therapies that include, but are not limited to, exercise training, education, and behavior change, designed to improve the physical and psychological condition of people with chronic respiratory disease and to promote the long-term adherence to health-enhancing behaviors (10) . It aims to enhance the functional capacity (11,12) , to reduce the frequency of the exacerbations (13) and hospital admission of patients with chronic lung disease (14) and, principally, to improve their QoL (11,15,16) . Although different studies show the benefits of the PR in COPD (11,12,15,17) and others respiratory chronic diseases (10) regarding inpatient or outpatient treatment (18,19) , somewhat is known about the physical training repercussions in candidates to lung transplant or lung transplant recipients (8,9) .…”
Section: Introductionmentioning
confidence: 99%
“…IPF patients tend to be older and predominantly male. 8,10,11 Consistent with those characteristics, ischaemic heart disease is the most frequent cardiovascular co-morbidity observed among IPF patients, with a prevalence ranging up to 68%, 12 and rates of first time events such as myocardial infarction more than twice that of age-and gender-matched patients without a diagnosis of IPF. 13 Coincidently, for patients with ischaemic heart disease, the evidence in support of cardiac rehabilitation is compelling.…”
mentioning
confidence: 62%
“…Although sample sizes have been relatively small, convincing evidence from meta-analysis demonstrates that although patients with IPF have a somewhat blunted response compared with other diagnoses, a twice a week programme of strength and endurance training provides short-term improvements in physical function (6-min walk test (6MWT)) that exceed the clinically meaningful difference, in addition to improvements in respiratory capacity, dyspnoea and quality of life. 9 In fact, Gaunaurd et al 10 reported that exercise training improves quality of life in IPF patients with much lower FVC% predicted than those described by Glaspole et al…”
mentioning
confidence: 97%